2005
DOI: 10.2106/jbjs.d.02942
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Dysplasia<sbt aid="1027210">Pathophysiology, Evaluation, and Treatment</sbt>

Abstract: Fibrous dysplasia is a common benign skeletal lesion that may involve one bone (monostotic) or multiple bones (polyostotic) and occurs throughout the skeleton with a predilection for the long bones, ribs, and craniofacial bones. The etiology of fibrous dysplasia has been linked to an activating mutation in the gene that encodes the alpha subunit of stimulatory G protein (G(s)alpha) located at 20q13.2-13.3. Most lesions are monostotic, asymptomatic, and identified incidentally and can be treated with clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
535
0
38

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(604 citation statements)
references
References 63 publications
8
535
0
38
Order By: Relevance
“…10,18,19,20,22 Rootman et al 18 have found the pattern to be equally distributed among the two groups, sclerotic and pagetoid. Others have found pagetoid to be the most common.…”
Section: Radiological Pattern Of Involvementmentioning
confidence: 97%
See 1 more Smart Citation
“…10,18,19,20,22 Rootman et al 18 have found the pattern to be equally distributed among the two groups, sclerotic and pagetoid. Others have found pagetoid to be the most common.…”
Section: Radiological Pattern Of Involvementmentioning
confidence: 97%
“…10 In our series, most patients had monostotic lesions that involved multiple adjacent bones and crossed suture lines, which is in agreement with that reported in other series. 19 However, distinction between monostotic and polyostotic forms can be difficult because of the intimate connection of the individual craniofacial bones. 20 In two major series, the frontal bone was involved in 58% of cases and the sphenoid in 35%.…”
Section: Radiological Pattern Of Involvementmentioning
confidence: 99%
“…To date, individual cases of osteosarcomatous, fibrosarcomatous and chondrosarcomatous degeneration have been observed, with the probability of degeneration being specified as approx. 0.4 % [22,23]. According to the literature, fibrous dysplasia is located on the cranial bones in 15 % of cases, primarily in the region of the paranasal sinuses and the jaw [24].…”
Section: Definition and Locationmentioning
confidence: 99%
“…There is also evidence that increased activity of osteoclasts are responsible for the expanding fibrous lesions which suggests treatment with bisphosphonates may be beneficial by inhibiting osteoclastic resorption of bone [16]. Radiographic features in fibrous dysplasia were well summarized in a paper by DiCaprio and Enneking [7]. They described the lesions as radiolucent with a grayish ''ground-glass'' pattern, occasionally with cystic areas.…”
Section: Discussionmentioning
confidence: 99%
“…They described the lesions as radiolucent with a grayish ''ground-glass'' pattern, occasionally with cystic areas. Lesions often have a distinct rim of reactive bone on its boundaries, irregular cortical contour, and variations in cortical thickness that may be secondary to ''endosteal scalloping'', referring to the slow resorption of the endosteal surface [7].…”
Section: Discussionmentioning
confidence: 99%